The Irish Economy: Three Strikes and You're Out? - GURDGIEV, CONSTANTIN; LUCEY, BRIAN MICHAEL (My University, 2011)
We examine the three interlinked Irish crises : the competitiveness, fiscal and banking crises, showing how all three combined to lay a lethal trap for Ireland. Starting from a point of economic balance, a series of poor government decisions led to the country once dubbed the ?Celtic tiger? become the second eurozone state after Greece to seek a bailout, with the EFSF/IMF intervening in late 2010.
PUBLISHED
Keywords: Economics; Banking; Debt